Honokiol Inhibits Melanoma Growth by Targeting Keratin 18 in vitro and in vivo - Liu, Tingting; Liu, Hui; Wang, Penglei; Hu, Yamei; Yang, Ran; Liu, Fangfang; Kim, Hong Gyum; Dong, Zigang; Liu, Kangdong (Frontiers in Cell and Developmental Biology, 2020)
Honokiol, a natural compound, derived from Magnolia officinalis, has been shown to have anti-cancer effect in several cancer types. However, the underlying molecular mechanism associated with its anti-cancer properties has not been fully elucidated. In the current study, we showed that honokiol inhibited the growth of melanoma cells in a dose and time-dependent manner. Mechanistically, it directly interacts with keratin 18 (KRT18) protein and induces its degradation through ubiquitination. Furthermore, the expression of KRT18 was found to be higher in melanoma tissues compared to the normal skin tissues. In addition, KRT18 overexpression significantly promoted melanoma cell proliferation and growth. Our results showed that honokiol treatment significantly decreased KRT18 protein level and suppressed the tumor growth in melanoma cell-derived xenograft mice models. Hence, KRT18 plays an oncogenic role in melanoma and honokiol can be an inhibitor for KRT18.